Antifungal activity of the essential oils of Cinnamomum zeylanicum and Minthostachys mollis on the strain Candida albicans - Li-Pereyra , Carmen del Pilar (2024)
Objectives: To determine the antifungal activity of two essential oils (EO), the EO of Cinnamomum zeylanicum (C. zeylanicum) at 100% and the EO Minthostachys mollis (M. mollis) at 100% on the strain of Candida albicans (C. albicans) ATCC 10231. Materials and Methods: The sample consisted of 45 cultures of C. albicans ATCC 10231 strains, divided into three groups: group 1: 100% C. zeylanicum EO, nystatin 100 000 IU/ml (positive control), sterile distilled water (negative control), group 2: 100% M. mollis EO, nystatin 100 000 IU/ml (positive control), sterile distilled water (negative control), and group 3: the combination of both essential oils and the corresponding positive and negative control used. The formation of growth inhibition halos was evaluated in millimeters. The Duraffourd scale was used to establish the sensitivity after 48 hours of incubation. Results: The 100% C. zeylanicum EO exhibited an average of 38.38 ± 3.32 mm growth inhibition zone, compared to the 100% M. mollis EO with an average of 35.61 ± 2.38 mm, the combination of 100% C. zeylanicum and M. mollis EOs (35.45 ± 3.82 mm). Conclusions: The antifungal activity of both C. zeylanicum and M. mollis EOs exhibits similarity in their antifungal activity against the C. albicans strain. However, it is not demonstrated that the antifungal activity of the combination of both EOs is superior to the antifungal activity on the M. mollis EO.